OPPORTUNITIES FOR THE IMPROVEMENT OF THE REQUIREMENTS APPLIED TO THE CANDIDATE FOR THE POSITION OF JUDGE (World Bulletin of Management and Law, 2023)
In the article, the requirements for the position of judge (citizenship, age and education) are studied and analyzed based on the legislation of foreign countries (Russian Federation, Tajikistan, Kazakhstan, Georgia, Azerbaijan, Belarus and Lithuania). In addition, the Law of the Republic of Uzbekistan “On Courts” states that certain terms defined as requirements for the position of judge need to be clearly explained in the law
Keywords: citizen; foreign citizen; age